Two decades under windmills: Energy transition and entrenched inequalities in La Venta, Mexico - Gerardo A. Torres Contreras (United Nations Research Institute for Social Development (UNRISD), 2020)
This paper seeks to analyse the process through which wind energy expansion has exacerbated patterns of rural inequality in La Venta, Mexico, the site of the first wind energy project in Latin America, established in 1994. Inequalities have arisen between landowners, and between landowners and landless people. Concerning landowners, wind energy rents have increased patterns of inequality among them because the wind industry reinforced long-standing inequalities in land ownership established with the foundation of the ejido-land that was collectively redistributed after the Mexican Revolution. In relation to landless people, they have been affected by a boom in the urban economy during the construction stage of the wind farms and a bust once the operational phase began, and by new kinds of exploitation resulting from non-agricultural labour. By analysing data on de-regularized landownership in the ejido and by drawing on fieldwork interviews, the paper shows that land has been concentrated in a few hands and that there has been a gradual productive shift from agriculture to cattle grazing activities. Asymmetric wind energy rents not only reinforce this trend but also result in different material and social relationships associated with wind energy, with actors benefiting from it in various ways-or not benefitting at all.
Keywords: 330; Isthmus of Tehuantepec; land inequalities; Mexico; renewable energy; wind power